Fatigue-related impairments in oculomotor control are prevented by norepinephrine-dopamine reuptake inhibition - Connell, Charlotte J. W. (Sci Rep, 2017)
Fatigue-induced reductions in saccade velocity have been reported following acute, prolonged exercise. Interestingly, the detrimental impact of fatigue on oculomotor control can be prevented by a moderate dose of caffeine. This effect may be related to central catecholamine upregulation via caffeine’s action as an adenosine antagonist. To test this hypothesis, we compared the protective effect of caffeine on oculomotor control post-exercise to that of a norepinephrine-dopamine reuptake inhibitor. Within a placebo-controlled crossover design, 12 cyclists consumed placebo, caffeine or a norepinephrine-dopamine reuptake inhibitor (bupropion) during 180 minutes of stationary cycling. Saccades, smooth pursuit and optokinetic nystagmus were measured using infrared oculography. Exercise fatigue was associated with an 8 ± 11% reduction in the peak velocity of prosaccades, and a 10 ± 11% decrement in antisaccade peak velocity. Optokinetic nystagmus quick phases decreased in velocity by 15 ± 17%. These differences were statistically significant (p < 0.05). Norepinephrine-dopamine reuptake inhibition and caffeine prevented fatigue-related decrements in eye movement velocity. Pursuit eye movements and visual attention were unaffected. These findings show that norepinephrine-dopamine reuptake inhibition protects oculomotor function during exercise fatigue. Caffeine’s fatigue-reversing effects on eye movements appear to be mediated, at least in part, via modulation of central catecholamines.